HUMAN RESOURCES MOTIVATION - A CHALLENGE FOR SMES ECONOMIC PERFORMANCES - POPESCU Dan; CHIVU Iulia; CIOCARLAN-CHITUCEA Alina; POPESCU Daniela-Oana (Annals of the University of Oradea: Economic Science, 2011)
The present research aims to establish and configurate human resources development strategies for the employees of small and medium-sized enterprises (SMEs) that activate in the tourism field of activity (hotels and other accomodation establishments, restaurants, passenger trasnport, travel agencies, cultural turism agencies). As knowledge role in the contemporany economy is increasing and defining the economical and social context as knowledge-based ones, we shall consider the research frame as the knowledge-based economy. Moreover, in order to better highlight weaknesses and strenghts of the human resources management approaches and to define recommendations, our research theme is developped as comparative study: similarities and differences within SMEs human resources management practices in Romania and other European Union's country members (the example of Spain was considered).